LEADERSHIP OF FEMALE SUB-DISTRICT IN PAKPAK ETHNIC PATRIARCHAL CULTURE IN SALAK DISTRICT - Ratih Baiduri; Melly Angella Sinaga (Universitas Negeri Medan, 2026)
This study aims to analyze the leadership characteristics of female sub-district heads based on transformational leadership theory, analyze the obstacles faced by female sub-district heads in carrying out their leadership duties in the midst of patriarchal culture and analyze the views of the community in Salak District towards the election of female sub-district heads as leaders in the midst of patriarchal culture. This study uses a qualitative research method with a descriptive approach with data collection techniques through observation, interviews and documentation. The results of the study show that the community and employees view female sub-district heads as having transformational leadership attitudes Idealize influence leadership attitudes that can be seen that sub-districts have attitudes as role models who are disciplined, firm, punctual, proactive and social, Inspirational motivation leadership attitudes that provide motivation in the form of verbal and moral motivation, Intellectual stimulation the attitude of the sub-district leadership that is open to ideas, suggestions and opinions for the progress of Salak District and Individualize consideration of leadership attitudes that pay attention to the needs of the community and its employees. The female sub-district head also does not get obstacles in terms of the patriarchal culture that exists in the Pakpak ethnic group because the Pakpak ethnic group has the motto Martampuk Bullung Merbenna Sangkalen, which means that everyone can position themselves according to their capacity and ability, in the sense that the motto provides an understanding of gender relations/openness. The community also views that to become a leader in the field of government for women is not an obstacle in terms of patriarchal culture in the Sulang Silima kinship system, where this kinship system only functions in positions in customs. Keywords: transformational leadership, women's sub-district, patriarchal culture